Methodology of comprehensive assessment of the athlete's adaptive potential to the load - A. A. Spassky; M. A. Myagkova; A. I. Levashova; S. K. Kukushkin; V. V. Kurshev; J. V. Yanova; L. V. Veselova (National Electronic Information Consortium (NEICON), 2020)
The review summarizes the current data on the methods of assessment of adaptation and disadaptation (fatigue, overreaching, overtraining, OT) of athlete during training; special attention is paid to the diagnostic value of biochemical and immunological markers of adaptation potential (AP). Their diagnostic significance was analyzed. Hypotheses and possible mechanisms of OT development were considered. Based on the results of recent studies published by domestic and foreign authors, both the diversity and the number of proposed adaptation markers have been established, and a lack of unity of approaches in the assessment of AP and OT has been revealed. Large amount of biochemical, immunological and other tests proposed for the evaluation of AP was summed up. The most significant AP and OT markers are protein metabolism factors, enzymes, lactate, urea. The role of immune factors, besides leukocytes and lymphocytes, is intensively studied: these are leukocyte toxicity index, level of neutrophils, cytokines, natural antibodies to AP bioregulators. The prospects of using an integrated test system for determining the e-At panel to AP bioregulators is shown for monitoring the athlete's condition, and especially for early diagnosis of OT.